1963
DOI: 10.1039/tf9635901181
|View full text |Cite
|
Sign up to set email alerts
|

Some reactions of cyclohexene with hydrogen and deuterium on evaporated gold films

Abstract: The reactions of cyclohexene with hydrogen or deuterium on gold films have been investigated using a mass spectrometer to analyze the products. Reactions of oyclohexene and hydrogen between 196 and 342°C yielded cyclohexane and benzene, the proportion of the latter increasing with temperature. Activation energies for the reactions were determined and the kinetics which showed some complex features were examined at 246°C. A simple exchange reaction occurred with cyclohexene and deuterium in the range 150-240" a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

1970
1970
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 2 publications
1
17
0
3
Order By: Relevance
“…Silica-, titania-and alumina-supported Au particles of 1-6 nm size, prepared by various synthetic routes were studied by Claus group in selective hydrogenation of acrolein, crotoaldehyde and 1,3-butadiene [24]. The very previous study on the reaction of cyclohexane with hydrogen on gold films [27] and gold powder [28] demonstrated that simultaneous dehydrogenation and hydrogenation of cyclohexane might occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica-, titania-and alumina-supported Au particles of 1-6 nm size, prepared by various synthetic routes were studied by Claus group in selective hydrogenation of acrolein, crotoaldehyde and 1,3-butadiene [24]. The very previous study on the reaction of cyclohexane with hydrogen on gold films [27] and gold powder [28] demonstrated that simultaneous dehydrogenation and hydrogenation of cyclohexane might occur.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Au in hydrogenation reactions has been investigated relatively recently [22][23][24][25][26][27][28][29][30][31][32][33]. This is because gold with a completely filled Au d-band has a limited ability to dissociate H 2 molecules [22].…”
Section: Introductionmentioning
confidence: 99%
“…Gold catalysts have been reported to hydrogenate a range of olefins, such as ethene [8], propene [9,10], pent-1-ene [11], cyclohexene [12,13], 1,3-butadiene [14,15], ethyne [16,17], propyne [18], but-2-yne [19], phenylacetylene [20] and aromatic compounds such as toluene and naphthalene [21]. Moreover, early work on gold films examined the hydrogenation of acetone to iso-propanol [22], although more recently, supported gold catalysts were reported to be inactive for the same reaction [23].…”
Section: Introductionmentioning
confidence: 99%
“…Gold catalyzes various hydrogenation reactions such as the hydrogenation of alkenes (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), alkadiens (13)(14)(15)(16)(17)(18) alkynes (13,(19)(20)(21)(22)(23)(24)(25), , -unsaturated carbonyl compounds and nitro compounds (47)(48)(49)(50)(51)(52)(53). In contrast to traditional hydrogenation catalysts such as platinum, palladium or ruthenium, which require modification, it often shows remarkable selectivities when multiple functional groups are present.…”
Section: Introductionmentioning
confidence: 99%